Genetic polymorphism of 3′ untranslated region of zeta-chain associated protein kinase 70 kDa in southern Taiwanese patients with rheumatoid arthritis. Issue 3 (March 2016) - Chen, Shih-Yao; Liu, Ming-Fei; Wang, Chrong-Reen
Abstract T cell activation participates in the pathogenesis of rheumatoid arthritis (RA), and the signaling molecule zeta-chain-associated protein kinase 70 kDa (ZAP-70) plays a crucial role in this process. Different mutations in the coding sequence of ZAP-70 are involved in a variety of immunological phenotypes, and recent evidence indicates that genetic variations within the 3′ untranslated regions (UTR) of microRNA binding sites may affect the hybridization with target mRNAs, leading to phenotype changes with disease status. In this study, we evaluated the possible effect of ZAP-70 polymorphism as a genetic risk factor in RA by examining the single-nucleotide polymorphism in 100 patients and 100 ethnicity- and sex-matched healthy individuals from southern Taiwan. In both groups, the genotype distribution of rs2278699 in the 3′ UTR was in the Hardy-Weinberg equilibrium. In RA, there were higher frequencies of the G allele (15.5 versus 8.0 %, odds ratio 2.1, P = 0.020) and significant differences in the trend of various genotypes (P = 0.024). The results suggest that genetic polymorphism in the 3′ UTR of ZAP-70 is associated with RA susceptibility in southern Taiwanese.